Diet in Acne Vulgaris: Open or Solved Problem? - Jakub MORZE; Katarzyna Eufemia PRZYBYLOWICZ; Anna DANIELEWICZ; Małgorzata OBARA-GOLEBIOWSKA (Tehran University of Medical Sciences, 2017)
Diet in Acne Vulgaris: Open or Solved Problem?